Design and Evaluation of Antimicrobial Coatings on Periodontal Probes to Mitigate Cross-Infection Risks - Anushree Choudhary; Niharika Benjamin; Bedkekar Sushma; Sheewali Saggar; Krishnan Hari; Muhamood Moothedath (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontal probes are essential tools in dental diagnostics, yet they pose a significant risk for cross-infection if not adequately sterilized. The development of antimicrobial coatings offers a promising approach to reduce microbial contamination on these instruments, thereby enhancing infection control measures. Materials and Methods: This study aimed to design and evaluate the efficacy of antimicrobial coatings applied to periodontal probes. A total of 50 stainless steel probes were divided into two groups: Group A (uncoated probes) and Group B (probes coated with a silver nanoparticle-based antimicrobial layer). The probes were subjected to microbial exposure using a standard inoculum containing Staphylococcus aureus and Escherichia coli. Colony-forming units (CFUs) were quantified before and after exposure to the coatings. The durability of the coating was assessed by repeated sterilization cycles and mechanical abrasion tests. Results: The antimicrobial coating significantly reduced microbial load, with Group B showing a 95% reduction in CFUs compared to Group A (P < 0.01). The coated probes maintained their antimicrobial efficacy after 30 sterilization cycles and demonstrated minimal wear during abrasion tests. No adverse effects on the structural integrity of the probes were observed. Conclusion: The application of antimicrobial coatings on periodontal probes is an effective strategy to reduce the risk of cross-infection. These coatings demonstrated robust antimicrobial properties and maintained durability under clinical conditions. Future research should explore the long-term clinical applicability and cost-effectiveness of this intervention.